The Most Frequently Asked Questions and Answers During Job Interviews at Hotels in Bali - Zefanya Wawointana; Anak Agung Sri Barustyawati; I Ketut Armawan (EDU SOCIETY: JURNAL PENDIDIKAN, ILMU SOSIAL DAN PENGABDIAN KEPADA MASYARAKAT, 2025)
This study aims to identify the most frequently asked job interview questions and answers during job interviews. This research uses a descriptive qualitative method, with data collection by distributing questionnaires to three subjects from the Human Resources Department. The research has been conducted from January 2024 - March 2025. This research is expected to provide insight into the types of questions commonly asked in job interviews, as well as help job seekers prepare answers that are more effective and in accordance with the expectations of the interviewer. The results of this study show that there are 27 most frequently asked questions and their answers during job interviews at Hotels in Bali.